On Tolerance in the 21st Century from the Aspect of Communicology, Political and Social Science : Text is published in periodical "Survey" 3-4, 2005 - Lazić, Tatjana (Pregled: časopis za društvena pitanja / Periodical for social issues, 2008)
One of the crucial parts of the post-structuralist philosophy of variety is to support variety with enthusiasm.The alternative to opening the gates of communication is defragmenting the modern to post-modern fragments that, standing alone have blurred shapes, but create different identification shapes and forms through interaction. A contemporary open communicative entity is understood to include the principles of permeability , interaction, tolerance and co-existence in order to create an objectivity of a multiple identity.